Credit System Based Learning Management in Serving Highly Intelligent Students in Madrasas - Fatoni, Ahmad; Wahyudi, Sahidin (Journal Corner of Education, Linguistics, and Literature, 2024)
This research aims to examine Credit System-Based Learning Management in Serving Highly Intelligent Students in Madrasas. This research method uses research and development methods and has the aim of improving Madrasah institutions. The average number of credits taken each semester is 40 credits. The research results show that the SKS based curriculum preparation model is used for students with fast learning characteristics, who require activities to compress material to find important material. Therefore, due to the use of credit-based curriculum in smart classes, there is an additional need to reduce the size of the curriculum. The SKS-based curriculum preparation model takes five steps. First, the number of lesson hours for all subjects throughout the year at Madrasah Aliyah is calculated. Then, the value of the package conversion to credits is divided by two, and then the conversion results, which are credit hours, are distributed throughout the semester. After that, each semester the number of credits that will be given from the beginning of the semester to the end of the semester is calculated. Once found, the total number of credits for each semester is divided by the number of study days (six days a week). If it has been found, it is ready to be held according to the demands for the number of credits charged in each subject.